(The Effect of Flour Mixture and CMC Addition on The Preparation of Ready To Used Mixed Flour for Friend Food Products) - Sutrisniati, Dwi; Mahdar, Dedi; Wiriano, Harry; Neffi Ridwan, Indra (Warta Industri Hasil Pertanian, 1995)
Ready to use mixed flour for fried food products had been made from rice flour and arenga starch, rice flour and tapioca, maize and arenga srarch and maize with tapioca. The comparison of flour applied was 45:55 and added with 0%,0.05% and 0.10% CMC.Ready to use mixed flour was aoolied in the fried food products such as tempeh chip.The result showed that the flour mixing affected the content of amylose and its viscosity,while CMC did not affect the amylose content, but the viscosity increased with the increasing CMC concertration. Organoleptic test (apperance, colour, taste , and flavor)of the fried food products was affected by compound mixed flour, but it was not affected by the addition of CMC in concertration up to 0.10%. The best composition of ready to use mixed flour was mixture of 45% rice flour and 55% arenga starch with 0.10% CMC,also 45%rice flour and 55% with 0.10% CMC.Â Â